Community-Based Strategies for Countering Fundamentalism, Radicalism, and Terrorism - Kristiantoro, Sony (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This study examines the role of community structures in preventing the emergence and growth of Fundamentalism, Radicalism, and Terrorism (FRT) using Cherian George’s Assertive Pluralism theory as its conceptual framework. The relevance of this research lies in the increasing challenges to social cohesion in pluralistic settings, including spatial segregation and exclusivist narratives that have the potential to fuel radicalisation. Employing a qualitative approach, the study draws on literature review, in-depth interviews, and field observations, focusing on an interfaith cooperation model developed in Salatiga City, Central Java, by the Salatiga Church Cooperation Agency (BKGS) in partnership with Muslim and Christian community networks. The findings reveal three main points. First, community-based organizations such as BKGS, Banser NU, Forum Hati Beriman, and the Interfaith Young Friends Movement (Gerakan Sobat Muda Lintas Iman) play a central role in fostering trust, solidarity, and mutual respect through interfaith collaboration in religious events, public services, and humanitarian programs. Second, interfaith education initiatives by UIN Salatiga and UKSW—through the integration of Islamology courses, halal studies, and the Kampus Kebangsaan program—strengthen interreligious understanding and engage students as agents of tolerance. Third, challenges remain, including the development of exclusive sharia housing, moral superiority narratives, rejection of interfaith activities, and weak assertiveness among local authorities, all of which can limit interfaith interaction and create fertile ground for radicalism. The study’s implications underscore the importance of synergy among four pillars—grassroots organizations, educational institutions, collaborative public initiatives, and responsive local governance—in community-based pre-conflict prevention. Its original contribution lies in the practical application of Assertive Pluralism in the Indonesian context, offering a conceptual model that can be replicated in other pluralistic regions to strengthen social resilience against FRT.